Reverse transduction can improve efficiency of AAV vectors in transduction‐resistant cells. Issue 12 (1st October 2018) - Lee, Esther J.; Robinson, Tawana M.; Tabor, Jeffrey J.; Mikos, Antonios G.; Suh, Junghae
Abstract: Reverse transduction, also known as substrate‐mediated gene delivery, is a strategy in which viral vectors are first coated onto a surface that subsequently comes into contact with mammalian cells. The cells internalize the surface‐attached vectors, resulting in transgene expression. We hypothesized that forcing the interaction between cells and adeno‐associated virus (AAV) vectors through a reverse transduction format would increase in vitro gene delivery efficiencies of the vectors in transduction‐resistant cells. We tested this hypothesis by comparing the gene delivery efficiencies of three AAV serotypes using either standard or reverse transduction approaches. Our study reveals reverse transduction of AAV7 and AAV9 can significantly improve their delivery efficiencies. In contrast, AAV2 does not perform better under the reverse transduction format. Interestingly, increased vector uptake by cells does not provide a complete explanation for the increased transduction efficiency. Our findings offer a simple and practical method for improving transduction outcomes in vitro in cell types less permissive to a particular AAV vector. Abstract : Reverse transduction, also known as substrate‐mediated gene delivery, is a strategy in which viral vectors are first coated onto a surface that subsequently comes into contact with mammalian cells. The cells internalize the surface‐attached vectors, resulting in transgene expression.